2017
DOI: 10.1007/s00439-017-1792-9
|View full text |Cite
|
Sign up to set email alerts
|

RNA splicing and splicing regulator changes in prostate cancer pathology

Abstract: Changes in mRNA splice patterns have been associated with key pathological mechanisms in prostate cancer progression. The androgen receptor (abbreviated AR) transcription factor is a major driver of prostate cancer pathology and activated by androgen steroid hormones. Selection of alternative promoters by the activated AR can critically alter gene function by switching mRNA isoform production, including creating a pro-oncogenic isoform of the normally tumour suppressor gene TSC2. A number of androgen-regulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
62
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(63 citation statements)
references
References 76 publications
1
62
0
Order By: Relevance
“…However, tumor cells are capable of producing abnormal proteins with altered, missing, or inserted domains, resulting in carcinogenesis . Recent studies have confirmed the close relationship between abnormal AS and oncogenic processes, including therapeutic resistance, tumor progression, and metastasis . Moreover, altered expression or mutations of splicing factors can result in global alterations in AS behavior, leading to oncogene and cancer pathway activation, and production of other cancer‐promoting splicing isoforms .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tumor cells are capable of producing abnormal proteins with altered, missing, or inserted domains, resulting in carcinogenesis . Recent studies have confirmed the close relationship between abnormal AS and oncogenic processes, including therapeutic resistance, tumor progression, and metastasis . Moreover, altered expression or mutations of splicing factors can result in global alterations in AS behavior, leading to oncogene and cancer pathway activation, and production of other cancer‐promoting splicing isoforms .…”
Section: Introductionmentioning
confidence: 99%
“…4 Recent studies have confirmed the close relationship between abnormal AS and oncogenic processes, including therapeutic resistance, tumor progression, and metastasis. [4][5][6][7] Moreover, altered expression or mutations of splicing factors can result in global alterations in AS behavior, leading to oncogene and cancer pathway activation, and production of other cancer-promoting splicing isoforms. [8][9][10][11] These findings suggest that tumor-specific splice variants might be effective diagnostic, predictive, and prognostic biomarkers, and may also be promising therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…31 Independent of DNA-level genetic mutations and alterations, alternative splicing represents another process by which a single gene can produce various Cancer February 15, 2020 mRNA and protein isoforms with related, distinct, or even opposing functional differences that can have profound biological consequences. 12,32,33 Using microarray analysis, we confirmed several tumor-specific splice variants of the LAMA3, DST, and TP63 genes in HNSCC, 34 and used RNA sequencing analysis to identify the oncogenic splice variant of AKT3 and DOCK5 in HPV-positive HNSCC and HPV-negative HNSCC, respectively. Alternative RNA splicing is one of the main cellular engines that expands the complexity and diversity of the eukaryotic proteome.…”
Section: Discussionmentioning
confidence: 81%
“…9 The genome-wide mapping of alternative splicing variants also has been identified in a variety of tumors, including gastric, prostate, and breast cancer as well as other tumors. 12,32,33 Using microarray analysis, we confirmed several tumor-specific splice variants of the LAMA3, DST, and TP63 genes in HNSCC, 34 and used RNA sequencing analysis to identify the oncogenic splice variant of AKT3 and DOCK5 in HPV-positive HNSCC and HPV-negative HNSCC, respectively. 15,16 In addition to a specific DOCK5 variant, a total of 580 ASEs associated with HPV-negative HNSCC were determined using outlier analysis, including the specific LOXL2 variant with a novel inserted exon.…”
Section: Discussionmentioning
confidence: 81%
“…It is still unclear whether drug toxicity can influence the phenotypes of mRNA isoforms, or whether drug-induced changes in mRNA isoform patterns is a key molecular mechanism by which drugs can interrupt gene function by switching mRNA isoform production. The androgen regulates a number of related genes to induce spliced mRNA isoforms, including a prostate-specific splice isoform of ST6GALNAC1 mRNA (Munkley et al 2017). Genetic rearrangements often occur in the early stages of diseases, leading to different patterns of alternative splicing and RNA isoforms in response to drug and to abnormal protein expression, synthesis, and activation.…”
mentioning
confidence: 99%